Functional Comparison of SCARB2 and PSGL1 as Receptors for Enterovirus 71 - Yamayoshi, Seiya (American Society for Microbiology, 2013)
Human scavenger receptor class B, member 2 (SCARB2), and P-selectin glycoprotein ligand-1 (PSGL1) have been identified to be the cellular receptors for enterovirus 71 (EV71). We compared the EV71 infection efficiencies of mouse L cells that expressed SCARB2 (L-SCARB2) and PSGL1 (L-PSGL1) and the abilities of SCARB2 and PSGL1 to bind to the virus. L-SCARB2 cells bound a reduced amount of EV71 compared to L-PSGL1 cells. However, EV71 could infect L-SCARB2 cells more efficiently than L-PSGL1 cells. The results suggested that the difference in the binding capacities of the two receptors was not the sole determinant of the infection efficiency and that SCARB2 plays an essential role after attaching to virions. Therefore, we examined the viral entry into L-SCARB2 cells and L-PSGL1 cells by immunofluorescence microscopy. In both cells, we detected internalized EV71 virions that colocalized with an early endosome marker. We then performed a sucrose density gradient centrifugation analysis to evaluate viral uncoating. After incubating the EV71 virion with L-SCARB2 cells or soluble SCARB2 under acidic conditions below pH 6.0, we observed that part of the native virion was converted into an empty capsid that lacked both genomic RNA and VP4 capsid proteins. The results suggested that the uncoating of EV71 requires both SCARB2 and an acidic environment and occurs after the internalization of the virus-receptor complex into endosomes. However, the empty capsid formation was not observed after incubation with L-PSGL1 cells or soluble PSGL1 under any of the tested pH conditions. These results indicated that SCARB2 is capable of viral binding, viral internalization, and viral uncoating and that the low infection efficiency of L-PSGL1 cells is due to the inability of PSGL1 to induce viral uncoating. The characterization of SCARB2 as an uncoating receptor greatly contributes to the understanding of the early steps of EV71 infection.